Desarrollo sostenible - Gudynas, Eduardo; Carpio Benalcázar, Patricio (Pontificia Universidad Católica del Perú, 2024)
In this article, different ideas of sustainable development are reviewed showing that they rest on ways of recognizing and assigning values. Despite its importance, this feature has not received the attention it deserves. The dominant valuation perspective is anthropocentric, which turns to behave as a conditionality that subordinates ecological imperatives and is functional to economic growth. Radical different perspectives are South American Andean-Amazonian alternatives based on a biocentric posture that recognizes intrinsic values in nature. Ecuador offers a case study of that perspective. It is argued that it represents a more powerful option because is an alternative beyond any variety of development.

En el presente artículo se revisan distintas concepciones del desarrollo sostenible para mostrar que descansan sobre modos de reconocer y asignar valores. Esta particularidad no ha recibido la atención que merece a pesar de su importancia. La perspectiva de valoración dominante es antropocéntrica, opera como una condicionalidad que subordina los imperativos ecológicos y es funcional al crecimiento económico. Esta se contrapone con alternativas andino-amazónicas elaboradas desde América del Sur, que responden a una perspectiva biocéntrica que reconoce valores intrínsecos en la naturaleza. Esa particularidad se ilustra para el caso de Ecuador. Se argumenta que representa una opción más potente al ser una alternativa más allá de cualquier variedad de desarrollo.
Sustainable Development
Keywords: Sustainable development; Nature’s rights; Economic growth; Anthropocentrism; Biocentrism; Desarrollo sustentable; Derechos de la naturaleza; Crecimiento económico; Antropocentrismo; Biocentrismo; https://purl.org/pe-repo/ocde/ford#5.04.00